Flexible Neural Interfaces Based on 3D PEDOT:PSS Micropillar Arrays (Adv. Mater. Interfaces 25/2022). Issue 25 (2nd September 2022) - Lunghi, Alice; Mariano, Anna; Bianchi, Michele; Dinger, Nikita Bhupesh; Murgia, Mauro; Rondanina, Eliana; Toma, Andrea; Greco, Pierpaolo; Di Lauro, Michele; Santoro, Francesca; Fadiga, Luciano; Biscarini, Fabio
Abstract : Flexible PEDOT:PSS Micropillar Arrays Flexible interfaces featuring 3D PEDOT:PSS micropillars are realized, showing tailored geometric area, surface properties and electrochemical characteristics as reported by Alice Lunghi, Michele Bianchi, Francesca Santoro, and co‐workers in article number 2200709 . Soft micropillars are shown to support the adhesion, growth and differentiation of SH‐SY5Y cells and influence the direction of neurite outgrowth, fundamental requirements for high‐performance neural interfaces.